1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Need help!

  1. Aug 30, 2010 #1
    got it thanks!
    Last edited: Aug 30, 2010
  2. jcsd
  3. Aug 30, 2010 #2
    homormophism. f(ab)=f(a)f(b) for all a,b in G

    so, imagine the domain and codomain, a will maps to f(a), b will map to f(b), so ab must map to f(ab)
    so it is homorphism if f(ab)=f(a)f(b)
  4. Aug 30, 2010 #3
    so, how does this relate to it being commutative? can we say that f(a)f(b)=f(b)f(a)?
  5. Aug 30, 2010 #4
    that is if and only if proof, so first assume it is homomorphism, so you know f(ab)=f(a)f(b)
    so you want to prove f(a)f(b)=f(b)f(a) or ab=ba, prove either one since both domain and codomain are G

    and conversely, assume that G is commutative, so you know ab=ba or f(a)f(b)=f(b)f(a) chose either one, to prove that f(ab)=f(a)f(b)
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook